An assessment of e-records readiness as a pre-requisite for e-governance in Tanzania: a case of selected public offices - Kamatula, Gwakisa (University of Dar es Salaam Library Journal, 2020)
E-Government is when the government owns or operates systems of information and communication technologies that transform relations with citizens, the private sector, and other government agencies so as to promote citizens ' empowerment, improve service delivery, strengthen accountability, increase transparency, and improve government efficiency (UNESCO, 2005). In order to have an effective implementation of e-government in the country, the availability of infrastructure and capacity necessary for the management of records and information in electronic environment (e-readiness) are crucial. This paper presents findings from a study that assessed the existing e-readiness for effective implementation of e-government in Tanzania. The study used two theories namely: the International Records Management Trust (IRMT) E-records Readiness Tool (2009) and World Bank E-government Handbook for Developing Countries (2002) as guidance. In the study, data were collected through interviews and personal observations and were analysed using thematic analysis. Findings of the study have revealed that despite the government's efforts to embrace ICT tools across the Tanzania public service, the management of e-records is not yet streamlined in many government offices. It was also evidenced during the study that record personnel, action officers, and IT staff were not conversant with procedures and practices of e-records management and had inadequate knowledge and skills pertaining to e-records and their related systems. Based on study findings, the paper recommends what needs to be done for effective e-readiness as a pre-requisite for e-governance across the public sector.